Topical resiquimod: a promising adjuvant for vaccine development?. (January 2010) - Igartua, Manoli; Pedraz, Joséé Luíís
Evaluation of: Chang BA, Cross JL, Najar HM, Dutz JP. Topical resiquimod promotes priming of CTL to parenteral antigens. Vaccine 27(42), 5791––5799 (2009). The development of vaccines for cancer and infectious diseases that require the predominant induction of cell-mediated immunity, including effective cytotoxic T lymphocyte (CTL) responses, remains a challenge. Over the past few years, numerous studies have demonstrated that targeting of antigens to immune receptors expressed by dendritic cells (DCs), such as Toll-like receptors (TLRs), elicits potent CTL responses. Therefore, the design of new adjuvants has focused on TLR agonists that elicit maturation of DCs to effectively link the innate and adaptative immune responses. The paper under evaluation describes the topical use of resiquimod, a TLR7/8 agonist, to enhance cross-priming to subcutaneously administered ovalbumin. The results obtained demonstrated that topical resiquimod is a potent adjuvant for subcutaneous vaccines, inducing clinically relevant antigen-specific CTL responses, which protect against B16-ovalbumin tumor challenge in mice.